Taxonomic amendments of Southeast Asian newt species of the genera Pachytriton, Paramesotriton and Laotriton (Amphibia, Urodela, Salamandridae) parasitized by water mites of the subgenus Lurchibates (Hydrachnidia, Hygrobatidae, Hygrobates) - Nishikawa, Kanto; Goldschmidt, Tom; Hiruta, Shimpei F.; Shimano, Satoshi (Zootaxa, 2020)
Hygrobates salamandrarum Goldschmidt, Gerecke and Alberti, 2002 (Acari, Hydrachnidia, Hygrobatidae) is the first-known water mite parasitizing adult newts. After its description, three further species of newt-parasitizing mites were described and the subgenus Lurchibates Goldschmidt and Fu, 2011 was proposed for the group, now containing four newt-parasitizing mites. Until now, each water mite species parasitizes a different newt species (Table 1), suggesting possible mite-newt co-speciation. In order to test this hypothesis, we need an accurate taxonomy of both of the hosts and parasites. However, the taxonomy of those Asian newt genera known to be parasitized by Lurchibates mites has been substantially revised after the initial description of the H. salamandrarum. To account for these taxonomic changes, we here revise the host-parasite species list and amend the host species name as shown in Table 1.